PENGEMBANGAN VIRTUAL LABS BERBASIS WEB DENGAN SIMULASI REAL-TIME UNTUK MENDUKUNG PEMBELAJARAN PRAKTIKUM ELEKTRONIKA - Galuh Kurnia Pratama; Endah Rahmawati; Arie Widodo (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Learning physics in the field of electronics is often considered difficult because the concepts are abstract and require direct practical experience. Limited laboratory facilities mean that many students do not have the opportunity to conduct experiments. The use of educational technology opens up opportunities to present digital simulations as an alternative to practical work. This research aims to develop the Virtual Labs Electronics website as a simulation-based learning medium designed to support the understanding of electronic concepts. The website development uses the ADDIE model by utilizing modern web technology to support system functionality, data management, and simulation visualization. The main product produced includes three main features, namely a realistic experiment module (resistor circuit, digital oscilloscope and logic gate), Complete Material, and Data Analysis. The website trial involved 15 student respondents through direct use and completion of a Likert scale questionnaire (1-5). Data were analyzed using descriptive statistics through calculating the average and feasibility percentage, and reinforced by qualitative analysis based on feedback. The results showed that all simulation features ran well on both laptop/PC and smartphone devices, with an overall average score of 4.5 with an average per indicator in the range of 4.4 - 4.6 and a feasibility level of 90%, thus categorizing it as